Social Network to Accelerate Agricultural Technology Adoption: Evidence from Hambanthota District, Sri Lanka - K. N. Nadeeshani Silva (Indian Journal of Extension Education, 2022)
Information links among the actors of social networks have a vital effect on the diffusion of knowledge from person to person and subsequently accelerate the adoption process. Poor information links led to the inefficiency of technology transfer and adoption by rural farmers in developing countries. Concerning the importance of information links of a social network on technology adoption, the study intended to explore the social network impact on the agricultural knowledge transferring process as an alternative extension approach over traditional extension practices. The 72 extension officers working in the Hambantota district were purposefully selected to collect primary data on information and knowledge network. Extension officers were identified as the key node of the information network. The role of contact farmers was prominent in paddy farming in Sri Lanka as they provided the interconnection between extension officers and farmers by sharing information. The study found that all the actors in the network similarly influenced each other and were well-connected. Further, the contact farmers’ approach can be successfully applied as a cost-effective extension tool in developing countries while progressing technology adoption among farmers.